Pengembangan Bahan Ajar Integratif Interaktif Berbasis Android pada Materi Statistika untuk Peserta Didik Kelas VIII: Development of Android-Based Interactive Integrative Teaching Materials on Statistics for Grade VIII Students - Mir’atul Khasanah; Abdul Halim Fathani; Siti Nurul Hasana (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study aims to develop integrative and interactive Android-based teaching materials on statistics, explicitly focusing on measures of central tendency and measures of data dispersion for eighth-grade students. This research was conducted using a research and development approach, adopting a 4D development model that comprises four stages: defining (Define), designing (Design), developing (Develop), and disseminating (Disseminate). In this study, the subjects included experts in the field of teaching materials and development, two practitioners, and six eighth-grade students from MTs Mambaul Ulum Pakis, who served as users. The final product is the Q-Stat learning application, which contains statistical materials based on the Merdeka Curriculum and is integrated with the values of the Qur'an and Hadith. This application features materials, practice questions, quizzes, and evaluations. The product was developed using Microsoft PowerPoint and iSpring Suite, then converted to run offline on Android devices. Validation results show that the developed application received a positive response. Material experts gave an average score of 4 (valid category), while teaching material development experts gave a score of 3.5. Practitioners gave an average score of 3.7, and students gave an average score of 3.5 (practical category). Based on these results, the Q-Stat application is considered valid and valuable. It can be effectively used in eighth-grade mathematics learning activities to support the understanding of statistical concepts in an integrative and interactive manner.